Performance of unit trust funds in Malaysia : a comparison between conventional and Islamic unit trusts / Rosma Mohd Dom ... [et al.] - Mohd Dom, Rosma; Ibrahim, Muhammad Fandi; Che Sulaiman, Che Lynnaruhiyah; Ahmad Sholahuddin, Ahmad Shafiq (Research Management Institute (RMI), 2014)
This paper reports the comparison of performance between Islamic and conventional unit trust funds in Malaysia. Least Square Methods were used to describe the overall growth of Malaysian unit trusts for the years 2004 to 2012 based on the number of launched funds, units in circulation, number of accounts and total net asset value. The results indicated that conventional unit trust funds grew exponentially while Islamic unit trusts grew linearly. The performances of 4 Islamic and 4 conventional unit trust funds based on their efficiencies (ratio of weighted sum of outputs to weighted sum of inputs) were measured using Data Envelopment Analysis over a three-year period (2010- 2012). The performances were measured based on two inputs namely the Portfolio Turnover Ratio (PTR) and Management Expense Ratio (MER) while the output was the companies’ annual returns. The outcome is the ranking of unit trusts performance which can be a good reference for investors. The finding shows that conventional unit trusts were the preferred investment among Malaysians. However, the growth of Islamic unit trusts was less affected by the world economic crisis compared to the growth of conventional unit trusts. This is reflected in the decrease of growth of the conventional unit trusts during the years 2007-2008, the time when the world economy was hit hard. On the contrary, the Islamic unit trust showed a gradually increasing growth during the same time period. CIMB conventional is found to be the best unit trust among the conventional unit trusts studied while Kuwait Finance House is found to be the best Islamic unit trust in this study, second only to CIMB conventional. Public Bank unit trust performed consistently on the average while AmBank showed poor performance throughout the years. CIMB conventional performed better than CIMB Islamic but RHB Islamic and AmBank Islamic performed better than their conventional counterparts.